1998
DOI: 10.1029/98wr02535
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and stretching efficiency in steady and unsteady groundwater flows

Abstract: Abstract. Mixing is the physical process through which solute is spread into a fluid by the stretching and folding of material lines and surfaces. Mixing, as compared to dilution, is important to solute spreading by groundwater because it operates on much shorter timescales than does dilution, and it provides the increased plume boundary area and high local concentration gradients that promote effective solute dilution. In this paper, the mixing process is investigated theoretically for subsurface tracer plume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…We refer to the latter process as mixing. Note that our definition of mixing differs from that of Weeks and Sposito [1998], who defined it as the stretching of the plume surface because of differences in advective transport. We think that our definition of mixing is more useful in the context of multicomponent reactive transport when different plumes belong to different compounds which may react when mixed Oya and Valocchi, 1998].…”
Section: Paper Number 1999wr900354mentioning
confidence: 74%
“…We refer to the latter process as mixing. Note that our definition of mixing differs from that of Weeks and Sposito [1998], who defined it as the stretching of the plume surface because of differences in advective transport. We think that our definition of mixing is more useful in the context of multicomponent reactive transport when different plumes belong to different compounds which may react when mixed Oya and Valocchi, 1998].…”
Section: Paper Number 1999wr900354mentioning
confidence: 74%
“…The mixing efficiency generally depends on the spatial variability of hydraulic conductivity (or transitions) between zones of highly contrasting hydraulic conductivities. Weeks and Sposito [1998] showed that mixing is driven by unsteady advection, which acts to stretch and fold fluid filaments in such a manner that plume boundary areas become highly irregular. Weeks and Sposito [1998] showed that the mixing of a solute plume by unsteady groundwater flow, in an aquifer with pronounced hydraulic conductivity variation, would be most effective if chaotic path lines were induced.…”
Section: Key Features Of Geometry and Nonlinear Dynamics Of Flow Thromentioning
confidence: 99%
“…Whenever H is constant and does not depend on data values, the quality of the reconstruction in areas with complex geometries is low. To solve this problem, Takeda et al 29 proposed to locally rotate and scale H to ensure that weight is concentrated along concentration isolines 14) where the overbar stands for averaging over the pixels adjacent to x i , and ÎŒ is a global smoothing parameter. This filter is nonlinear because H i depends now on the solution through ∇u.…”
Section: ■ Introductionmentioning
confidence: 99%